Financial Statement Fraud: Testing Of Hexagon Fraud And Green Competitive Advantage With Audit Committee Moderation - Whittleliang Hakki , Tandry; Akwila, Karvicha; Jurjanta, Priccilya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Financial statement fraud is a scheme in which an employee intentionally causes a misstatement or omission of material information in a company's financial statements. This study aims to analyze the effect of Fraud Hexagon on Financial Statement Fraud and the effect of Green Competitive Advantage on financial statement fraud. This researcher also aims to analyze the role of the Audit Committee as a moderator of the effect of Fraud Hexagon and Green Competitive Advantage on Financial Statement Fraud. Based on the results of the study, it shows that financial targets have a significant effect on financial statement fraud. Accrual Ratio has a significant effect on financial statement fraud. Ineffective monitoring does not have a significant effect on financial statement fraud. Changes in directors do not have a significant effect on financial statement fraud. External pressure has a significant effect on financial statement fraud. Project cooperation has a significant effect on financial statement fraud. Green Competitive advantage does not have a significant effect on financial statement fraud. The Audit Committee strengthens the influence of Financial Targets on Financial Statement Fraud. The Audit Committee strengthens the influence of Accrual Ratio on Financial Statement Fraud. The Audit Committee does not strengthen the influence of Ineffective Monitoring on Financial Statement Fraud. The Audit Committee does not strengthen the influence of Changes in Directors on Financial Statement Fraud. The Audit Committee does not strengthen the influence of External Pressure on Financial Statement Fraud. The Audit Committee strengthens the influence of Project Cooperation on Financial Statement Fraud. The Audit Committee does not strengthen the influence of Green Competitive Advantage on Financial Statement Fraud.